Seeking conceptual clarity in the action modalities - Joseph A. Raelin (Action Learning: Research and Practice, 2009)
This article begins with the presumption that action learning has not made as deep an impact in promoting participatory social change as its supporters may have hoped for, but nor has its cousin action modalities, such as action research and action science. These action strategies have evolved separately along distinct traditions and, rather than focus on their commonalities, their proponents have tended to cite their differences from one another. As a result, they have seldom stood together to advocate for their shared epistemology based on practice as the fundamental unit of analysis. Accordingly, after briefly summarizing the history and differences among these action modalities, this article will focus on their potential confederation. It cites ten unifying elements that may construct an agenda characterized by the value of learners collectively reflecting on planned engagements that can not only expand but can create knowledge while at the same time serving to improve practice.
Keywords: J24; M10; M53; M12; 330; Action learning; Action research; Action science; Practice; Tacit knowledge; Experiential education